2015
DOI: 10.1111/dar.12244
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a group cessation program for co-smokers of cannabis and tobacco

Abstract: Introduction and Aims: This study aims to evaluate the feasibility and effects of a group cessation program for cannabis and tobacco co-smokers. Design and Methods: Using a repeated-measures design with pre-, post-and six months follow-up assessments, feasibility (intervention utilisation, safety and acceptability) and changes in substance use behaviour and mental health were evaluated. The intervention consisted of five to six group sessions and was based on current treatment techniques (e.g. motivational int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…For example, in a study of substance abuse program directors who also had clinical responsibilities, Richter (2006) found that the directors urged their patients to delay quitting smoking because they believed that patients should not try to change too many things at one time. However, recent studies have found that targeting tobacco during treatment for cannabis use disorders did not negatively impact marijuana outcomes (Becker, Haug, Kraemer, & Schaub, 2015;Lee et al, 2014). Additional studies are needed to identify effective prevention and treatment interventions for marijuana and tobacco co-users (Ramo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of substance abuse program directors who also had clinical responsibilities, Richter (2006) found that the directors urged their patients to delay quitting smoking because they believed that patients should not try to change too many things at one time. However, recent studies have found that targeting tobacco during treatment for cannabis use disorders did not negatively impact marijuana outcomes (Becker, Haug, Kraemer, & Schaub, 2015;Lee et al, 2014). Additional studies are needed to identify effective prevention and treatment interventions for marijuana and tobacco co-users (Ramo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies were RCTs [39][40][41][42][43][44][45]47,48,[60][61][62] and eight were pilot or feasibility ('uncontrolled') studies [37,38,46,49,[56][57][58][59]. Fourteen studies were from the United States, two from Switzerland, two from the United Kingdom, one from France and one from Australia.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Technology-based interventions and group interventions might serve as effective methods to reach African Americans who are less likely to engage in traditional treatment (Becker et al, 2012) and more likely to cite support as a necessary and important component of treatment (Burgess et al, 2014). For example, in a predominately White sample of adult cannabis and tobacco co-users participating in a group cessation program (MI/CBT and self-control training) for co-users, participants reported significant decreases in tobacco and cannabis use over a 6-month period (Becker, Haug, Kraemer, & Schaub, 2015). A similar approach might also work well for African Americans who use cannabis and tobacco.…”
Section: Discussionmentioning
confidence: 99%